Analisa Pencarian Data *.Doc pada Komputer Menerapkan Metode Sequensial With Sentinel - Frengki Santoso (STMIK Budi Darma, 2019)
In the development of computers often encounter problems about how to get a data in a large data set and various types of data. In its need to find that data, there are various search algorithms, namely the sequential with Sentinel method. Searching is data search by searching where the data is searched. The place for searching the data can be an array in memory, it can also be in a file in external storage. When the amount of data is already so large, a method is needed to get the data needed. Several methods of organizing data have made the process of finding data more efficient. In the problem that often occurs a lot of lost doc data dimension or forget the name of the stored data and therefore applied how to find doc document data that is on the computer. A data contained in the storage media with this search method is created using a search algorithm that uses successive method so that the data sought knows its whereabouts. in overcoming the problem is applied The method of doc data extension can be done in two ways, namely internal search (internal searching) and external search (external searching). In an internal search, all records that are known to be in a computer reminder are on an external search, not all records that are known to be in a computer reminder.